Environmental assessment of ashes generated from medical waste incineration - Mohamad Rahim, Fariha Liana (2015)
The nature of medical waste itself, which comprises of human pathological waste, items saturated or dripping with human blood, hypodermic needles etc. poses serious health threat to community, especially concerning spreading of infectious diseases, as well as causing pollutions to the environment. Incineration is one of the technologies adopted in many part of the world in dealing with medical wastes. However the process emits pollutants including toxic heavy metals, which are dispersed via the incineration stack, either vented directly to the atmosphere or are emitted after going through treatment in air pollution control unit. Meanwhile the remaining heavy product is concentrated into bottom and fly ash residues which are normally present in very small concentration or known as trace elements (TEs). This study was conducted to determine the concentration of TEs in bottom ash and fly ash of medical waste incinerator plant in Malaysia. In addition, it is a vital to understand the TEs behaviour and to assess the capability of the existing air pollution control (APC) technologies in Malaysia to comply with the new emission limits of the Environmental Quality (Clean Air) Regulation 2014 which replaces the Malaysia Environmental Quality (Clean Air) 1978. In this study, the APC designed with the electrostatic precipitator (ESP), fabric filter and spray scrubber with limestone were comply with the new specified emission limits but it need further improvement to improve the efficiency. The comparison of TEs behaviour in term of volatility; most volatile element (Hg) and less volatile element (Cr, Cd, As, Pb) in fly ash and bottom ash was also presented in this paper. The study showed that the samples of bottom ash and fly ash enriched of heavy metals of Pb, followed by As, Cd, Cr, and Hg. In environmental assessment, all of these TEs are found to be well below the Malaysian Department of Environment (DOE) Scheduled Waste Guideline limits except for Pb in fly ash which is above the emission limits. It is indicated that behaviour of TEs is related to TEs concentration in ash. In addition, the concentration of TEs also influenced the emission of TEs in flue gas.